Performance testing of a low power consumption wireless sensor communication system integrated with an energy harvesting power source - Marsic, Vlad; Giuliano, Alessandro; Pozzi, Michele; Zhu, Meiling; Williams, Stewart W. (Cranfield University, 2012)
This paper presents the performance testing results of a wireless sensor communication system with low power consumption integrated with a vibration energy harvesting power source. The experiments focus on the system’s capability to perform continuous monitoring and to wirelessly transmit the data acquired from the sensors to a user base station, completely battery-free. Energy harvesting technologies together with system design optimisation for power consumption minimisation ensure the system’s energy autonomous capability demonstrated in this paper by presenting the promising testing results achieved following its integration with Structural Health Monitoring (SHM) and Body Area Network (BAN) applications.